Equivalence of computer codes for calculation of coincidence summing correction factors – Part II. (March 2016) - Vidmar, T.; Camp, A.; Hurtado, S.; Jäderström, H; Kastlander, J.; Lépy, M-C.; Lutter, G.; Ramebäck, H.; Sima, O.; Vargas, A.
Abstract: The aim of this study was to check for equivalence of computer codes that are capable of performing calculations of true coincidence summing (TCS) correction factors. All calculations were performed for a set of well-defined detector parameters, sample parameters and decay scheme data. The studied geometry was a point source of 133 Ba positioned directly on the detector window of a low-energy (n-type) detector. Good agreement was established between the TCS correction factors computed by the different codes. Highlights: Equivalence of computer codes used for calculation of TCS corrections was checked. Codes were compared with each other for a well-defined detector and sample model. All the codes used the same DDEP decay scheme data. A simulated 133 Ba point source was placed onto the window of an n-type detector. Good agreement was found between the results of the different computer codes.